2022
DOI: 10.3389/fpls.2022.872054
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Complexity in Strawberry Fruit Development and Maturation Revealed by Nanopore Sequencing

Abstract: The use of alternative transcription start or termination sites (aTSS or aTTS) as well as alternative splicing (AS) produce diverse transcript isoforms, playing indispensable roles in the plant development and environmental adaptations. Despite the advances in the finding of the genome-wide alternatively spliced genes in strawberry, it remains unexplored how AS responds to the developmental cues and what relevance do these outcomes have to the gene function. In this study, we have systematically investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…Intriguingly, most AS-occurring genes were also accompanied by aTSS and aTTS. Furthermore, the frequencies of aTSS and aTTS were more common than that of AS, which was consistent with the observations in human genes [ 30 ] and also similar to the response to fruit development and maturation of strawberry genes [ 10 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Intriguingly, most AS-occurring genes were also accompanied by aTSS and aTTS. Furthermore, the frequencies of aTSS and aTTS were more common than that of AS, which was consistent with the observations in human genes [ 30 ] and also similar to the response to fruit development and maturation of strawberry genes [ 10 ].…”
Section: Discussionsupporting
confidence: 89%
“…Usually, AS events are commonly classified into intron retention, exon skipping, the alternative 5′ splice site, the alternative 3′ splice site, and mutually exclusive exons, and the occurrence of these changes could impact the fate of gene products. Alternative transcription initiation and alternative transcription termination are also important transcriptional regulation processes that contribute to transcript complexity in plants [ 10 ]. Based on single molecular long-read sequencing data, we identified that 27,244 genes produced at least two isoforms in growing culms, suggesting the vital function of AS, aTSS, and aTTS in moso bamboo culm growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study identified 506 sex-biased alternative splicing events in the antennal tissue of Bactrocera dorsalis, with ATSS accounting for 31% of these events. This phenomenon of ATSS having a relatively high proportion in alternative splicing events has also been found in other species (Reyes and Huber, 2018;Chen et al, 2022). Currently, there are a lack of studies on the relationship between ATSS events and inter-sexual differentiation of gene functions in insects.…”
Section: Discussionsupporting
confidence: 59%
“…This study identified 506 sex-biased alternative splicing events in the antennal tissue of Bactrocera dorsalis, with ATSS accounting for 31% of these events. This phenomenon of ATSS having a relatively high proportion in alternative splicing events has also been found in other species (Reyes and Huber, 2018;Chen et al, 2022). Currently, there are a lack of studies on the relationship between ATSS events and inter-sexual differentiation of gene functions in insects.…”
Section: Discussionsupporting
confidence: 59%